Дослідження символіки та семантики опису тіла героїв від дастана «Огузнаме» до «Книги Деде Коркута» - Алі Дуймаз (Народна творчість та етнографія, 2010)
With extraordinary qualities, epic heroes are of ideal types of societies. For this reason they have psychologically and physically more different characteristics than ordinary people have. Extraordinary qualities attributed to epic hero are mainly stated by various symbols. This condition can be seen Oguz body descriptions in Oguz Kagan Epic, being on the position of prototype of Turkish epics and The Book of Dede Korkut, being qualified as the last ring of tradition of Oguzname. In this study, some topics like hero descriptions, symbols in these descriptions, the meaning of the very symbols, and the causes of using these symbols are evaluated in the context of Oguz Kagan and Dede Korkut. By doing so, some conclusion on the belief and value systems of people who created these telling, their political and social structure, cosmic curiosity, universe and perception of object are reached.